Public memory and popular culture: biopics, #MeToo, and David Foster Wallace. Issue 2 (15th March 2021) - Sheldon, Zachary
ABSTRACT: Public memory scholars contend that depictions of a figure can never be definitive, but the "biopic" genre of film complicates this. Biopics may be an audience's only exposure to a figure, lending them great significance in determining how culture remembers the individuals portrayed. This phenomenon is explored through the biopic The End of the Tour, memorializing writer David Foster Wallace. The way that the film advances a specific reading of Wallace's life has implications for the ways that popular culture informs the perpetuation of certain public memories. That Wallace's story has been complicated by the #MeToo movement further implicates popular media in the formation of public memory. This article demonstrates how biopics embody the functions and form of epideictic rhetoric, and addresses issues of how epideictic power is accrued in media such as biopics in the contemporary neoliberal era. Wallace and The End of the Tour offer a unique opportunity to examine such issues due to fluctuations in his public reputation across the span of his life and death. Recognizing the consequences of mediated, neoliberal epideictic raises possibilities for future explorations of the relation between power and memory today.